THE LEVEL OF ADVERBS IN UZBEK LINGUISTICS (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
Arabic grammar, which is recognized today as the most perfect grammar, was also advancing at a rapid pace, as were Indian, Greek, and Chinese linguistics. The emergence and development of linguistics in the Arab Caliphate was also associated with practical needs, i.e. during this period there was a great difference between the ancient monuments and the language of the Qur’an and the living Arabic language. The research carried out by Arab scholars in order to make the Qur'an understandable and to protect the classical Arabic language from the influence of dialects has reached us in some of the scientific works.